FAKTOR-FAKTOR YANG MEMPENGARUHI KECEMASAN MATEMATIKA PADA SISWA SMA - , RINI RISNAWITA SUMINTA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aimed to: (1) assessing whether the variable of parental academic support, peer academic support and classroom climate on mathematics anxiety directly and (2) assessing whether the variable mathematics self-efficacy and flow mediated parental academic support, peer academic support and classroom climate on mathematics anxiety. The population in this research consists all students of SMA in Kediri, East Java. The sample was as many as study 765 students, taken through multi-stage cluster sampling and simple random sampling method. The data collection techniques used in this research was scales and checklists. There were five types of scales used in the data collection process